Supporting the transition to higher education: examination of state- and trait-level effects of a multicomponent positive psychological intervention for university students - Ewert, Christina; Palme, Lou; Voigt, Wilhelm H. A.; Tomczyk, Samuel (Frontiers in Psychology, 2025)
IntroductionPositive psychological interventions (PPIs) can help mitigate psychological challenges and facilitate the transition to higher education.MethodsThis study presents the results of a quasi-experimental trial of a 6-week universal, multicomponent PPI designed specifically for university students. It compares survey responses of intervention group participants with those of passive control group participants before, immediately after, and 6 months after the intervention.ResultsThe results show that the PPI led to significant improvements in mindfulness, positive reframing, and self-compassion at the trait level, and in self-compassion, positive affect, relaxation, subjective physical health, and subjective sleep quality at the state level.DiscussionThe study demonstrates that PPIs can effectively build psychological resources during educational transitions, particularly those related to emotion regulation. However, other resources and outcomes (e.g., character strengths) were less affected. Thus, more tailored approaches and selective interventions are recommended to address these areas comprehensively and ensure a more holistic improvement in student wellbeing.